(untitled) (Bangladesh Journal of Public Administration, 2024)
This study examines the motivational factors behind the migration of Bangladeshi migrants to Libya and identifies the risks and challenges faced by the migrants associated with their voluntary return to their home country. Incorporating this evidence from the literature reviews and the key informants’ interviews, this research demonstrated lack of fixed source of income is the main push factor for migration followed by social and community level pressures for better income generation and higher income opportunity is the main pull factor for migration followed by the aspiration to settle down in Europe, especially in Italy as the final destination. It is also observed that the magnitude of difficulties and challenges experienced by the Bangladeshi migrants in Libya are higher than the driving forces for migration, leading to the voluntary return to their home country. This phenomenon of the voluntary return of the Bangladeshi migrants from Libya must be addressed through a combination of adequate reintegration support, building social awareness, pertinent counselling for the returnees, proper coordination among the parties involved in the repatriation and reintegration process and appropriate policy intervention with a view to discourage the unplanned migration for the potential migrants.